Reasons for the Limited Involvement of Potential Future Users in the Design Process: Technological and Architectural Solutions for Blind People - Gajoch, Paulina (Inclusive Digital Technologies: Perspectives, Opportunities, and Limitations, 2025)
Modern approaches to product and service design increasingly emphasize the importance of involvingend-users in the creation process. Tis article discusses the theoretical foundations of userconsultations, as well as design methods that incorporate their perspectives. Subsequently, the articleanalyzes the consequences of neglecting such consultations by examining the thread named„Absurdalne ułatwienia i rozwiązania utrudniające życie niewidomych” from the Elten forum(a community of Polish blind people). Te aim of this study is to highlight how disregarding potentialusers’ opinions leads to inefective and impractical designs that may even hinder the dailylives of the very individuals they aim to assist.